Novel genipin cross-linked chitosan-silk fibroin sponges for cartilage engineering strategies - Silva, Simone Santos (2008)
The positive interaction of materials with tissues is an important step in regenerative medicine strategies. Hydrogels that are obtained from polysaccharides and proteins are expected to mimic the natural cartilage environment and thus provide an optimum milleu for tissue growth and regeneration. In this work, novel hydrogels composed of blends of chitosan and Bombyx mori silk fibroin were cross-linked with genipin (G) and were freeze dried to obtain chitosan/silk (CSG) sponges. CSG sponges possess stable and ordered structures because of protein conformational changes from R-helix/random-coil to -sheet structure, distinct surface morphologies, and pH/ swelling dependence at pH 3, 7.4, and 9. We investigated the cytotoxicity of CSG sponge extracts by using L929 fibroblast-like cells. Furthermore, we cultured ATDC5 cells onto the sponges to evaluate the CSG sponges’ potential in cartilage repair strategies. These novel sponges promoted adhesion, proliferation, and matrix production of chondrocyte-like cells. Sponges’ intrinsic properties and biological results suggest that CSG sponges may be potential candidates for cartilage tissue engineering (TE) strategies.